Keterpautan 23 Marka Mikrosatelit pada Kromosom 6 dan 7 dengan Karakter Ketahanan Populasi Jagung terhadap Penyakit Bulai (Peronosclerospora maydis) - Roberdi, Roberdi S; Aswidinnoor, Hajrial S; Setiawan, Asep S; Sutrisno, Sutrisno S; Pabendon, Marcia B; Azrai, Muhammad S (Jurnal AgroBiogen, 2010)
Linkage of 23 Microsatellite Marker on Chromosome 6and 7 to Downy Mildew Resistance on Maize. Roberdi,Hajrial Aswidinnoor, Asep Setiawan, Sutrisno, Marcia B.Pabendon, and M. Azrai. Downy mildew caused byPeronosclerospora is one of most important maize diseasein several countries, including Indonesia. Parental andprogenies selection based on conventional breeding is timeconsuming and laborious. Development of molecularbiology produces many DNA markers used for selection, oneof them is microsatellite. The aim of this research to identifymicrosatellite markers associated with downy mildewresistance on maize progeny MR-4 X AMATLCOHS-9-1-1-1-1-1-2-B, on chromosome 6 and 7. This research was consistedof two activities, phenotypic and genotypic analysis.Phenotypic analysis used 175 progenies BC1F2 and both ofparents. This analysis included planting of spreading row,inoculums preparation, inoculation of spreader rows, testmaterial planting, inoculation of test material andobservation. Genotypic analysis used 175 progenies BC1F1and both of parents. This analysis included DNA genomeisolation, PCR analysis, electrophoresis, gel staining and datascoring. Percentage of downy mildew infections on MR-4was 76%, while these on AMATLCOHS-9-1-1-1-1-1-2-B was16%, and on 175 progenies had range from 10.1-100%. Out of23 SSR, 12 markers could be mapped in chromosome 6 and11 markers in chromosome 7. QTL analyses showed thatchromosome 7 contain one QTL in position between phi082and phi116I marker as far as 18.6 cM with 2.6 LOD value.